ANTIINFLAMMATORY PROPERTIES OF DICHLOROMETHANE: METHANOLIC LEAF EXTRACTS OF CAESALPINIA VOLKENSII AND MAYTENUS OBSCURA IN ANIMAL MODELS - Maina, Mwangi B.; Maina, Gitahi S.; Muriithi, Njagi J.; Kiambi, Mworia J.; Umar, Aliyu; Ann, Njoroge W.; John, Mwonjoria K.; Piero, Ngugi M.; David, Mburu N. (International Journal of Current Pharmaceutical Research, 2015)
Objective: Inflammation is the reaction to injury of the living tissues. Conventional medication of inflammation is expensive and arguably associated with various severe adverse effects hence the need to develop herbal agents that are effective as alternative. Caesalpinia volkensii and Maytenus obscura are plants that grow in Mbeere County of Eastern region of Kenya. This study was designed to evaluate the anti-inflammatory activity of C. volkensii and M. obscura plants. Methods: Experimental animals were divided in to four groups; normal group, diseased negative control group, diseased reference group and diseased experimental groups. Inflammation was inducted into the mice using carrageenan. The experimental groups were treated with leaf extracts of the plants at concentration of 50 mg/kg, 100 mg/kg and 150 mg/kg. Anti-inflammatory activities in rats were compared with diclofenac (15 mg/kg) as the standard conventional drug. Results: The leaf extracts of C. volkensii reduced the paw edema by between 6.50%-13.42% while the extracts of M. obscura reduced it by between 4.94%-22.36%. Diclofenac reduced the paw edema by between 4.11%-10.47%. Conclusion: The phytochemical screening results showed that the extracts of C. volkensii had flavonoids, steroids and phenolics while the leaf extracts M. obscura had phenolics, terpenoids and saponins. Flavonoids, saponins and phenolics have been associated with anti-inflammatory activities. Therefore, the study has established that the DCM: methanolic leaf extracts of Caesalpinia volkensii and Maytenus obscura are effective in management of inflammation.